Fostering Children's Solidarity Through Donations for Palestine - Hisan, Khairatun (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service activity with the theme "Caring for Palestine: Your Resilience and Endurance Are an Inspiration for Us" at TPQ Darul Ihsan aims to raise awareness and concern about the humanitarian conditions faced by the Palestinian people. For a long time, Palestine has been a symbol of struggle and resilience in the face of oppression. Through this activity, the people of Aceh, especially the younger generation, are expected to cultivate empathy and solidarity for the Palestinian struggle. This activity includes education about the history and current situation in Palestine, fundraising to help ease the burden on the Palestinian people, and a children's creativity competition with a Palestine theme. In addition, this activity aims to instill values of resilience and endurance in children, which are expected to serve as motivation in facing life's challenges. This activity also serves as a bridge between the people of Aceh and Palestine, strengthening solidarity among Muslims and building social awareness in the local community. With a spirit of togetherness, this activity is expected to have a positive impact not only on Palestine but also on the young generation involved.